A biomechanical analysis of lower limb movement on the backcourt forehand clear stroke among badminton players of different levels - Zhao, X.; Li, S. (Applied Bionics and Biomechanics, 2019)
Most of the previous studies have been focused on the upper limb biomechanical characteristic in the clear stroke among different level badminton players, but research on the lower limb is limited. The aim of this study is to explore the lower limb kinematics and foot pressure in the backcourt forehand clear stroke among badminton players to give theoretical reference in teaching and answer the questions occurring in the process of learning the actions. Ten professional badminton players (PP) and ten amateur players (AP) were recruited in this study. Plantar pressure analyses indicated that both the PP and the AP were in contact with the ground over the forefoot without the midfoot and heel. The work suggests that when designing professional badminton sports shoes, the designers should focus on strengthening footwear resistance in the metatarsal and forefoot area, especially the first metatarsal area, to meet the requirement of the movement demand and take the badminton movement characteristics in different regions of the design. The peak ankle dorsiflexion, eversion, and internal rotation angle levels of the AP are lower than those of the PP. It is important for the AP group to enhance their ankle strength to prevent injury and improve performance.